PENDAMPINGAN DOSEN DAN MAHASISWA DALAM MENINGKATKAN UMKM DI BIDANG USAHA HOME INDUSTRY DI PASAMAN BARAT - Anhar Harahap (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article discusses the important role of students in supporting Micro, Small and Medium Enterprises (MSMEs) in the home industry sector. Students have the potential to make diverse contributions through their knowledge, skills and initiative in improving the UKM home industry. This article also identifies the challenges that the UKM home industry often faces, including limited resources, market access, operational management, and intense competition. Students can help overcome these challenges through effective collaboration. In addition, this article discusses the contribution of students in product and process innovation, which can help the UKM home industry to become more competitive. Students can provide an understanding of market research, new product design, production process optimization, technology development, employee training, and much more. This helps MSMEs face tough competition and improve the quality of their products. Marketing and product visibility are also the focus of this article, explaining how students can help the MSME home industry in utilizing social media, websites, SEO optimization, visual content and other digital marketing strategies. With good collaboration, local products can be better known by a wider market, which has the potential to increase UKM income. Benefits of good financial management for UKM. Proper financial management gives UKM a better understanding of their financial performance, helps in decision making, and enables them to plan their budgets better. This also helps MSMEs in meeting their tax obligations and increasing their business desirability.